PROBLEMATIKA PENCATATAN PERNIKAHAN DI KUA KECAMATAN KOTO PARIK GADANG DIATEH KABUPATEN SOLOK SELATAN PASCA PENERAPAN SISTEM INFORMASI MANAJEMEN NIKAH BERBASIS WEBSITE - Nurlen hamidah; Salma Salma (Jurnal AL-AHKAM, 2021)
In the Regulation of the Minister of Religion of the Republic of Indonesia Number 34  of  2016  concerning  the Organization  and  Work  Procedures of  the Sub-District Religious Office Article 3 paragraph 1 (a) it is stated that in carrying out the duties of the  District  KUA(Religious  Affairs  Office),  it  carries  out  functions  which  include carrying out services, recording marriages and reporting marriages and reconciliation. Furthermore, the Regulation of the Minister of Religion of the Republic of Indonesia Number 20  of  2019 concerning  Marriage Registration  in detail the function. PMA Number 20 of 2019 concerning Marriage Registration is a substitute for the previous PMA, namely PMA Number 19 of 2018 concerning Marriage Registration because the PMA is no longer in accordance with current developments and needs. PMA Number 20 of 2019 states that: marriages between a man and a Muslim woman must be recorded in the Marriage Certificate carried out by the Head of the District KUA or PPN LN. The Web-based Marriage Management Information System application known as SIMKAH web  was  launched  by  the  Ministry  of  Religion  of  the  Republic  of  Indonesia  on November 8, 2018. The launch was a follow-up to the memorandum of understanding between  the  Minister  of  Religion  and  the  Minister  of  Home  Affairs  Number: 470/5711/SJ and Number 20 of 2015 concerning Cooperation in Utilization Population Identification Number, Population Data and Electronic ID Card within the Scope of the Ministry of Religion. But in practice there are several things that become problems in the process of registering marriages on the SIMKAH Web application. One of them is the discrepancy in the data of the bride and groom. The actual bride data is different from the data contained in the SIMKAH Web application which is connected to SIAK in the Civil Registry.